Workability & mechanical properties of the single and hybrid basalt fiber reinforced volcanic ash-based cement mortars after freeze–thaw cycles. (February 2023) - Guler, Soner; Funda Akbulut, Zehra
Abstract: This study examines the workability, mass loss, relative dynamic modulus of elasticity (RDME), residual compressive strength (RCS), and residual flexural strength (RFS) of single and hybrid basalt (BA) fiber-reinforced cement (BAFRC) mortars after freeze–thaw (F-T) cycles. Volcanic ash (VA) was used in all mixtures by replacing 10% with cement. Two micro and one macro-BA fiber were added to cement mortars as single and hybrid forms at 0.5% and 1% volume. All specimens were exposed to 24, 48, and 72F-T cycles in a 3% sodium chloride (NaCl) solution. The changes in the microstructural properties of control and BAFRC specimens after F-T cycles were also examined with scanning electron microscope (SEM) analysis. The results showed significant decreases in all specimens' mass loss, RDME, RCS, and RFS values after F-T cycles. Although the single and hybrid-BA fibers significantly reduce the workability of the mortars, they are slightly effective in increasing the RCS and RFS capacities of the mortars after F-T cycles. Furthermore, BA fibers contribute a little to reducing the mass losses of the mortar after F-T cycles. In addition, the hybrid use of BA fibers is more effective than single BA fibers in increasing mortars' RCS and RFS capacities after F-T cycles, as they provide a more robust fiber/matrix interface.